Territórios em conflito no alto sertão sergipano - Tanezini, Theresa Cristina Zavaris (2014)
The thesis entitled “Territories in conflict in Alto Sertão Sergipano” proposes a critical reflection as the study objective, of two distinct and conflictive social-territorial processes, based in land appropriation: on one hand, the territory expansion and monopolization by capital, hegemonic and linked to capital accumulation in a national and international scale, understood as an unequal and combined development; and, on the other hand, the resistance and landing recreation as the alternative expansion; analyzing the State’s contradictory role regarding the conflictive territoriality, which spatially demonstrates the conflicts between classes in the fields. Adopting Critical Geography as theoretical and methodological reference, the social space is understood as the place where production social relationships happen, which is a result of the production process of the space by capital confronting the social-territorial movements, with a relative approach of the creation of territory, which emphasizes the T-D-R geographical processes; regarding the social conflicts, as a geographical version of the agrarian matter. This study aimed to analyze the empirical processes that were historically developed in the production and transformation of the agrarian landscape in Sergipe’s most arid area. This thesis defends three main ideas: the first one is the land acquisition by social-territorial movements, mainly the MST (acronym for Landless Workers Movement) and the massive agrarian redistribution which highlights the experience of agrarian reform in this geographical space, a point of inflection in the territorial dispute, reverting the capital advance, it enabled the reconstitution of landless workers by establishing them in their place as peasants; the second one is the configuration of the reformed area and the alliances between the established agrarian workers and the traditional peasants, through their social movements, starting to demand, as a group, their acknowledgement as political subjects and economic agents who manage a comprehensive and significant agrarian territory; the third idea discussed is that this alternative territory questions and also interferes in the predominant space of the social and political supreme order. Results from the research show that 6,092 families organized by the MSTR, religious pastoral groups, MST, in addition to the Xocó indigenous group and the African Quilombola communities (Mocambo and Serra da Guia), between 1979 and 2014, conquered 104,612.28 hectare. The agrarian structure has been radically altered: from the figure of 12,728 properties and 390,716 hectare registered (INCRA, 2013), only 5 land properties of 1,000 hectare each (0.03% of the total area) have remained, which covered 6,392 hectare (1.6% of the total area). In 48 settlements 1,575 families keep fighting for the democratization of the land. In the dispute for water supplies control, the business watered perimeter Jacaré-Curitiba was converted into the agrarian reform and there are settlements in the future perimeter Nova Califórnia and the region of the Xingó Canal. In conclusion, the social-territorial movements were successful in expanding territories for most part of the non-productive and productive properties, making it possible for land, wealth and income to be properly distributed.